2005
DOI: 10.1186/1743-422x-2-59
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and cytokines in the early defence against herpes simplex virus

Abstract: Herpes simplex virus (HSV) type 1 and 2 are old viruses, with a history of evolution shared with humans. Thus, it is generally well-adapted viruses, infecting many of us without doing much harm, and with the capacity to hide in our neurons for life. In rare situations, however, the primary infection becomes generalized or involves the brain.Normally, the primary HSV infection is asymptomatic, and a crucial element in the early restriction of virus replication and thus avoidance of symptoms from the infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 438 publications
(405 reference statements)
3
49
0
1
Order By: Relevance
“…4), the F 1 and F 2 fractions resulted in considerable mRNA expression of these cytokines, whereas relatively little mRNA expression was observed with the F 3 fraction. In general, pro-inflammatory mediators such as TNF-␣, IL-1␤, IL-6 and PGE 2 are essential for host survival from injured and/or abnormal [14,20,21]. These cytokines could be produced by the stimulation of immune cells, including T-cells, B-cells and macrophages.…”
Section: No Release and Inos Mrna Expressionmentioning
confidence: 99%
“…4), the F 1 and F 2 fractions resulted in considerable mRNA expression of these cytokines, whereas relatively little mRNA expression was observed with the F 3 fraction. In general, pro-inflammatory mediators such as TNF-␣, IL-1␤, IL-6 and PGE 2 are essential for host survival from injured and/or abnormal [14,20,21]. These cytokines could be produced by the stimulation of immune cells, including T-cells, B-cells and macrophages.…”
Section: No Release and Inos Mrna Expressionmentioning
confidence: 99%
“…Published data show that interferon-α (IFN-α) is also involved in the early nonspecific defense response to herpes infection [8]. As compared to sensitive mice, resistant animals are characterized by earlier activation of IFN-α (after 2 h) and autocrine IFN-α/β-regulated respiratory burst [4]. It should be emphasized that the increase in IFN-α/β activity depends on activation of the intracellular receptor TLR9.…”
Section: Resultsmentioning
confidence: 99%
“…This process is determined by various components of the innate immune response [3,5]. Macrophages produce an antiviral effect on HSV within the first hours after infection [4]. It should be emphasized that HSV is an intracellular pathogen, and macrophages can phagocytize HSV.…”
mentioning
confidence: 99%
“…Overall, HBV reactivation is much more common [23, 24] and this is thought to be due to the required involvement of TNF α in the host immune response to HBV infection [25, 26]. Similarly, the role of TNF α in host defense mechanisms against the herpes simplex virus is thought to be important and likely involves macrophage activation and immune cell signalling [27]. Mouse models have demonstrated that TNF α depletion leads to rapid reactivation of HSV-1 infections and TNF α knockout mice are more susceptible to primary HSV-1 infection and had higher subsequent rates of mortality [28].…”
Section: Discussionmentioning
confidence: 99%